Sacred Resentment - Gans, Eric Lawrence (2020)
Given my thesis that love is "the transcendence of resentment," one might ask why both in the name of these Chronicles and in the last two of them love precedes resentment. No doubt in the first case one can allege the superior euphony of the word order, but a more serious justification must be found...